Pengaruh Akuntabilitas dan Transparansi terhadap Pengelolaan Anggaran - Hery Harjono Muljo; Heny Kurniawati; Pahala Pahala (Bina Nusantara University, 2014)
The purpose of this study is to determine the relationship of the application of the principles of good governance such as the principles of accountability and transparency, which is carried out on budget management. The method is quantitative approach. Three hypotheses is proposed in this study. First, whether accountability affects Budget Management, second, whether Transparency affects the Budget Management and third, whether Accountability and Transparency does affect the Budget Management. Research states that accountability is positively associated with budget management, transparency is also positively related to budgetmanagement, and Accountability, and Transparency together positively related to budget management.